ASSESSMENT OF GENETIC DIVERSITY OF SOME NATIVE GRAPEFRUIT VARIETIES (CITRUS GRANDIS) IN VIETNAM USING SIMPLE SEQUENCE REPEAT MICROSATELLITES MARKERS - Trung, Khuất Hữu (Vietnam Journal of Biotechnology, 2011)
Citrus is native to China, Eastem India, Vietnam and Southeast Asia. The information on level of genetic diversity and origin is very important for conservation gene resource, selection and development of commercially important grapefi-uit. Thirty-five simple sequence repeat (SSRs) markers were used to detect molecular polymorphisms among 29 Citms accessions from 11 native grapefruit varieties in Vietnam. A total of 115 alleles were detected with an average of 3.29 alleles per locus; polymorphism information content (PIC) value range from 0.0 to 0.82, with an average of 0.45. All grapefruit accessions showed heterozygosity from 35.26 to 51.61%. Genetic similarity was determined using Jaccard’s similarity coefficient and final dendrogram construction using a UPGMA clustering methods showed that 29 accessions were divided into 8 distinguished heterotic groups with genetic similarity from 0.32 to 1.0. The obtained results could be useftil for germplasm fingerprinting, preeminet selection and proper utilization in breeding programs